A comparative analysis of cross border travel influences at the port level: Pacific Highway/Douglas, B.C. — Blaine, WA and Windsor, ON — Detroit, MI. (September 2015) - Burke, Charles M.
Abstract: Cross border travel is important for local business. The majority of cross border travel is undertaken as day trips which concentrate spending in a few locales. Such spending can be critical to the success of stores, sports, events, and restaurants on either side of border. This study undertakes a comparative analysis of the largest Western border port and the largest Midwestern border port over the past 17 years. A time series analysis of crossing volumes at the two ports uncovers factors that influenced changes in cross border travel over that time period. Based on the results of two time series regression models (one for each port), we find enhanced security post 9/11 and the exchange rate influenced changes in volumes at each port, while declining income in the Windsor region factored in declining cross border travel in that region.